2021
DOI: 10.3762/bjoc.17.94
|View full text |Cite
|
Sign up to set email alerts
|

Fritsch–Buttenberg–Wiechell rearrangement of magnesium alkylidene carbenoids leading to the formation of alkynes

Abstract: A series of 1-heteroatom-substituted vinyl p-tolyl sulfoxides were prepared and treated with organometallic reagents to evaluate which combination of sulfoxides and organometallic reagents yielded alkynes the most efficiently. The use of 1-chlorovinyl p-tolyl sulfoxide and isopropylmagnesium chloride was optimal for this purpose. A variety of 1-chlorovinyl p-tolyl sulfoxides were prepared from carbonyl compounds and chloromethyl p-tolyl sulfoxide and were converted into alkynes via the sulfoxide/magnesium exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…In our previous study, we have found that the 1,2-rearrangement, called a Fritsch-Buttenberg-Wiechell (FBW) rearrangement, 11 of magnesium alkylidene carbenoids 2 gives alkynes 3. 12 If excess Grignard reagents are used for this reaction, the resulting terminal alkynes 3 are expected to be deprotonated by Grignard reagents to give alkynylmagnesium chlorides. In this paper, we describe the generation of alkynylmagnesium chlorides from 1chlorovinyl p-tolyl sulfoxides 1 and Grignard reagents via the sulfoxide/magnesium exchange reaction, the FBW rearrangement of magnesium alkylidene carbenoids 2, and the deprotonation of terminal alkynes 3 with Grignard reagents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we have found that the 1,2-rearrangement, called a Fritsch-Buttenberg-Wiechell (FBW) rearrangement, 11 of magnesium alkylidene carbenoids 2 gives alkynes 3. 12 If excess Grignard reagents are used for this reaction, the resulting terminal alkynes 3 are expected to be deprotonated by Grignard reagents to give alkynylmagnesium chlorides. In this paper, we describe the generation of alkynylmagnesium chlorides from 1chlorovinyl p-tolyl sulfoxides 1 and Grignard reagents via the sulfoxide/magnesium exchange reaction, the FBW rearrangement of magnesium alkylidene carbenoids 2, and the deprotonation of terminal alkynes 3 with Grignard reagents.…”
mentioning
confidence: 99%
“…In our previous study, toluene was a suitable solvent for FBW rearrangement. 12 However, the reaction of sulfoxide (Z)-1a, 3.5 equivalents of isopropylmagnesium chloride, and benzaldehyde in toluene gave terminal alkyne 3a in 98% yield, and the desired propargyl alcohol 4a was not obtained (entry 1). The deprotonation of terminal alkyne 3a with isopropylmagnesium chloride in toluene was seemingly sluggish, although the sulfoxide/magnesium exchange reaction and FBW rearrangement occurred with high efficiency.…”
mentioning
confidence: 99%